2021
DOI: 10.1111/jep.13547
|View full text |Cite
|
Sign up to set email alerts
|

From intention to action: A systematic literature review of provider behaviour change‐focused interventions in physical health and behavioural health settings

Abstract: Rationale, aims and objectives: It is clear there are significant delays in the uptake of best practices as part of routine care in the healthcare system, yet there is conflicting evidence on how to specifically align provider behaviour with best practices. Method: We conducted a review of interventions utilized to change any aspect of provider behaviour. To extend prior research, studies were included in the present review if they had an active intervention targeting behaviour change of providers in health or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Our goals for the tool were to (1) increase frequency of health care provider information-sharing conversations with caregivers of children with a DSD and (2) improve the quality of those conversations by incorporating best practice components of disclosure interventions. Therefore, we designed the tool keeping in mind the literatures on both health care provider behavior change (Gupta et al, 2021) and models for health information disclosure (Greene et al, 2012; Rochat et al, 2013; Schulte et al, 2021). Both areas of literature highlight the importance of providing tailored, contextually relevant information as well as behavioral rehearsal to increase self-efficacy.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Our goals for the tool were to (1) increase frequency of health care provider information-sharing conversations with caregivers of children with a DSD and (2) improve the quality of those conversations by incorporating best practice components of disclosure interventions. Therefore, we designed the tool keeping in mind the literatures on both health care provider behavior change (Gupta et al, 2021) and models for health information disclosure (Greene et al, 2012; Rochat et al, 2013; Schulte et al, 2021). Both areas of literature highlight the importance of providing tailored, contextually relevant information as well as behavioral rehearsal to increase self-efficacy.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Provider perceptions of lack of time in addition to usual clinical duties was an expected barrier in this pilot, given the new, untested nature of the system and the general challenges of affecting provider behavior change. Including multiple, active, and contextually relevant behavior change strategies, such as continuing education incentives, might help overcome this barrier [ 20 , 21 ]. In fact, we found that the barrier of perceived duplicated work effort was no longer identified as a barrier by participants at the end of the pilot study, suggesting that users may have dropped processes made obsolete by DialysisConnect (eg, phone calls).…”
Section: Discussionmentioning
confidence: 99%